Experimental infection of some bacterial fish pathogens in the cichlid fish, Oreochromis mossambicus - Omprakasham, M; Manohar, L (Indian Journal of Fisheries, 2011)
Bacterial strains of Pseudomonas fluorescein (NCIB), Pseudomonasfluoresceins (ATCC), Pseudomonasputida (NClB),Escherichia coli (NCIB) and Proteus vulgaris (NCIM) were inoculated intoOreochromis mossambicus through different routes of administration and observed for external andinternal pathological changes. The dropsical condition, the typical symptom of bacterial haemorrhagicsepticaemia, was observed in only those fish which were injected with Ps.fluorescens through parenteralroute of administration, while the scarification method produced variations with the 2 different strains. Ps.putida showed low virulence and pathogenicity. E. coli caused pronounced enteritic conditions. The fishhowever, did not respond to Pr. vulgaris, by all the 3 routes of administration. The varying degrees ofsusceptibility is interpreted as due to the strain virulence of the bacterial pathogens tested and thesusceptibility of the fish species.